Blood-Brain Barrier Abnormalities Caused by HIV-1 gp120: Mechanistic and Therapeutic Implications - Jean-Pierre Louboutin; David S. Strayer (The Scientific World Journal)
The blood-brain barrier (BBB) is compromised in many systemic and CNS diseases, including HIV-1 infection of the brain. We studied BBB disruption caused by HIV-1 envelope glycoprotein 120 (gp120) as a model. Exposure to gp120, whether acute [by direct intra-caudate-putamen (CP) injection] or chronic [using SV(gp120), an experimental model of ongoing production of gp120] disrupted the BBB, and led to leakage of vascular contents. Gp120 was directly toxic to brain endothelial cells. Abnormalities of the BBB reflect the activity of matrix metalloproteinases (MMPs). These target laminin and attack the tight junctions between endothelial cells and BBB basal laminae. MMP-2 and MMP-9 were upregulated following gp120-injection. Gp120 reduced laminin and tight junction proteins. Reactive oxygen species (ROS) activate MMPs. Injecting gp120 induced lipid peroxidation. Gene transfer of antioxidant enzymes protected against gp120-induced BBB abnormalities. NMDA upregulates the proform of MMP-9. Using the NMDA receptor (NMDAR-1) inhibitor, memantine, we observed partial protection from gp120-induced BBB injury. Thus, (1) HIV-envelope gp120 disrupts the BBB; (2) this occurs via lesions in brain microvessels, MMP activation and degradation of vascular basement membrane and vascular tight junctions; (3) NMDAR-1 activation plays a role in this BBB injury; and (4) antioxidant gene delivery as well as NMDAR-1 antagonists may protect the BBB.